The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1467-8268.12539
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and entrepreneurship willingness of youth: Evidence from Mali

Abstract: This study examines the determinants of youth financial inclusion and its impacts on their willingness to become entrepreneurs in Mali. The World Bank's Global Findex database is used to perform Logit estimations and propensity score matching. We find that the financial inclusion of youth seems to be more determined by the attainment of a high level of education, employment status, living in a wealthy family, and having at least one family member with a bank account. Three factors appear as barriers to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This strategy is particularly relevant as some factors such as distance to a financial institution (9.2%), transaction costs (10.1%) and the required documents (41.8%) drive Africans toward mobile accounts. Indeed, the results highlight that these factors, associated with lack of trust in institutions, negatively affect the ownership of traditional accounts, which is in line with Koloma (2021), who demonstrated that the lack of money was the key barrier to formal inclusion in Mali. Thus, financial institutions must promote proximity to improve the perception of potential clients about the services.…”
Section: Empirical Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This strategy is particularly relevant as some factors such as distance to a financial institution (9.2%), transaction costs (10.1%) and the required documents (41.8%) drive Africans toward mobile accounts. Indeed, the results highlight that these factors, associated with lack of trust in institutions, negatively affect the ownership of traditional accounts, which is in line with Koloma (2021), who demonstrated that the lack of money was the key barrier to formal inclusion in Mali. Thus, financial institutions must promote proximity to improve the perception of potential clients about the services.…”
Section: Empirical Results and Discussionsupporting
confidence: 81%
“…For instance, using the 2014 database on 37 African countries with probit estimations, Zins and Weill (2016) found that being a man, richer, more educated and older enables financial inclusion, with a higher influence of income and education. Soumaré et al (2016), Koloma (2021) and Senou and Manda (2022), focusing on Central and West Africa and using the endogenous switching regression technique, propensity score matching and logit estimations, showed that age, gender, residence area, income, education, employment, marital status, household size, having one family member with a bank account and a degree of trust in financial institutions were driving financial inclusion. However, these results differ from one country to another.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that the least vulnerable people in society are more likely to be excluded financially. Indeed, Koloma (2021) finds that the financial inclusion of youth is mainly curtailed by the high cost of financial services and the lack of money. In contrast, Senou et al (2019) and Jack and Suri (2011) find that younger people are more likely to adopt mobile money.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ssonko and Kawooya (2020) further emphasized that cost factors such as mobile money service providers' surcharges, over‐the‐counter taxes and the cost‐benefit comparison of mobile money service and traditional brick and mortar financial service providers will affect the sustainability of the uptake of mobile money services during and after the pandemic. Before the pandemic, previous studies highlighted the role of transaction costs in deterring financial inclusion through mobile financial services (Bair & Tritah, 2019; Koloma, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value youths place on rural entrepreneurship is that, despite their apparent financial poverty, careers are about much more than making money. Many youths aspire to start their rural activities, including agricultural businesses, despite the lack of skills, role models and access to finance (Ataei et al, 2020;Koloma, 2021;Metelerkamp et al, 2019;Njangang et al, 2020).…”
mentioning
confidence: 99%